If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7b + 7c + -1(8a * 78d) = 0 Reorder the terms for easier multiplication: 7b + 7c + -1(8 * 78a * d) = 0 Multiply 8 * 78 7b + 7c + -1(624a * d) = 0 Multiply a * d 7b + 7c + -1(624ad) = 0 Remove parenthesis around (624ad) 7b + 7c + -1 * 624ad = 0 Multiply -1 * 624 7b + 7c + -624ad = 0 Reorder the terms: -624ad + 7b + 7c = 0 Solving -624ad + 7b + 7c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7b' to each side of the equation. -624ad + 7b + -7b + 7c = 0 + -7b Combine like terms: 7b + -7b = 0 -624ad + 0 + 7c = 0 + -7b -624ad + 7c = 0 + -7b Remove the zero: -624ad + 7c = -7b Add '-7c' to each side of the equation. -624ad + 7c + -7c = -7b + -7c Combine like terms: 7c + -7c = 0 -624ad + 0 = -7b + -7c -624ad = -7b + -7c Divide each side by '-624d'. a = 0.01121794872bd-1 + 0.01121794872cd-1 Simplifying a = 0.01121794872bd-1 + 0.01121794872cd-1
| g(x)=(x^2-3x-4)(x^2-1) | | 13g=7g+54 | | 7n+8=(-20) | | 7n+8=6 | | k=9k+28 | | 8y-14z=7 | | 8y-13z=7 | | 6y-13z=7 | | 4xy+5y=3x-2 | | 6-6x-4=-3+3x-13 | | 2x=10y-20 | | x^2-10*x-81=0 | | 2x=-8y+34 | | 6k+5k=11 | | 23(12x+18)=36 | | 3sin^2(3x)+3cos^2(3x)=0 | | 5n-25=10 | | 5n+25=10 | | 3(x-2)+4x=-5 | | -x^2+2x-1.1=0 | | x^2-2x+1.1=0 | | 3(x-2)+4x=5 | | a=0.2bh | | -6x+6-(-4x-1)=4x-3 | | 7=12(4x-8) | | -12-16.8= | | 9x^2+12x+29=0 | | x^8-6x^7+9x^6-x^2+6x+9=0 | | X=-12-4(4.2) | | 9x^2+12+29=0 | | x+(x-10)+(x-24)=0 | | 2(x+3)=3(1-2x) |